Direct visualization of the modulated field distribution along single gold nanowires by differential interference contrast microscopy. Issue 37 (7th September 2016) - Ha, Ji Won
Abstract : DIC microscopy enables us to visualize the modulated field distribution along single gold nanowires. Abstract : This paper describes the optical properties of micrometer-long gold nanowires studied by differential interference contrast (DIC) microscopy. A far-field DIC microscope enables us to visualize the modulated field distribution along the nanowires resulting from the interference of the longitudinal surface plasmon resonance (SPR) modes and the linearly polarized incident light. Therefore, we demonstrate a new way of using far-field DIC microscopy to elucidate the relationship between incident light and the induced plasmon modes on single nanowires.